Rupture and Migration Law of Disturbed Overburden during Slicing Mining of Steeply Dipping Thick Coal Seam - Shuai Liu; Ke Yang; Chunan Tang; Xiaolou Chi (Advances in Civil Engineering)
Steeply inclined and thick coal seams in Huainan Panbei Coal Mine in Anhui Province, China, were analyzed by physical analog modeling, acoustic emission (AE), and distributed fiber sensing (DBS). The secondary deformation breakage law, sound, and light response characteristics in the rock mass deformation process induced by lower slice mining of steeply inclined coal seams were determined. The results show that the mutation of the hinged rock beam structure in the lower region and the cantilever beam structure in the upper region of the lower slice disturbed overburden is the main cause of the rupture of the workface roof. Based on the AE energy and distributed fiber strain response characteristics, the six stages of disturbed overburden instability in the lower slice and cyclic patterns of steeply inclined coal seams were revealed. The key prevention and control areas of the workface were found to be related to the disturbed high-level immediate roof rupture during the lower slice mining process, rupture of the disturbed main roof, and sliding of disturbed overburden. The three-stage AE positioning morphological characteristics and DBS response stepped jump patterns were analyzed in detail. The research results are considered instrumental in the combined AE and DBS monitoring of deformation and damage of rock and soil structures.